Inhibitory effect of lactobacilli supernatants on biofilm and filamentation of Candida albicans, Candida tropicalis, and Candida parapsilosis - Poon, Yeuklan; Hui, Mamie (Frontiers in Microbiology, 2023)
Probiotic Lactobacillus strains had been investigated for the potential to protect against infection caused by the major fungal pathogen of human, Candida albicans. Besides antifungal activity, lactobacilli demonstrated a promising inhibitory effect on biofilm formation and filamentation of C. albicans. On the other hand, two commonly isolated non-albicans Candida species, C. tropicalis and C. parapsilosis, have similar characteristics in filamentation and biofilm formation with C. albicans. However, there is scant information of the effect of lactobacilli on the two species. In this study, biofilm inhibitory effects of L. rhamnosus ATCC 53103, L. plantarum ATCC 8014, and L. acidophilus ATCC 4356 were tested on the reference strain C. albicans SC5314 and six bloodstream isolated clinical strains, two each of C. albicans, C. tropicalis, and C. parapsilosis. Cell-free culture supernatants (CFSs) of L. rhamnosus and L. plantarum significantly inhibited in vitro biofilm growth of C. albicans and C. tropicalis. L. acidophilus, conversely, had little effect on C. albicans and C. tropicalis but was more effective on inhibiting C. parapsilosis biofilms. Neutralized L. rhamnosus CFS at pH 7 retained the inhibitory effect, suggesting that exometabolites other than lactic acid produced by the Lactobacillus strain might be accounted for the effect. Furthermore, we evaluated the inhibitory effects of L. rhamnosus and L. plantarum CFSs on the filamentation of C. albicans and C. tropicalis strains. Significantly less Candida filaments were observed after co-incubating with CFSs under hyphae-inducing conditions. Expressions of six biofilm-related genes (ALS1, ALS3, BCR1, EFG1, TEC1, and UME6 in C. albicans and corresponding orthologs in C. tropicalis) in biofilms co-incubated with CFSs were analyzed using quantitative real-time PCR. When compared to untreated control, the expressions of ALS1, ALS3, EFG1, and TEC1 genes were downregulated in C. albicans biofilm. In C. tropicalis biofilms, ALS3 and UME6 were downregulated while TEC1 was upregulated. Taken together, the L. rhamnosus and L. plantarum strains demonstrated an inhibitory effect, which is likely mediated by the metabolites secreted into culture medium, on filamentation and biofilm formation of C. albicans and C. tropicalis. Our finding suggested an alternative to antifungals for controlling Candida biofilm.